Efficacy and safety of semi-flexible thoracoscopic cryobiopsy in the diagnosis of elderly tuberculous pleurisy. (2020) - Jo, Tatsunori; Kuse, Naoyuki; Inomata, Minoru; Awano, Nobuyasu; Tone, Mari; Takada, Kohei; Yoshimura, Hanako; Bae, Yuan; Kumasaka, Toshio; Izumo, Takehiro
Abstract: Background: Thoracoscopic pleural biopsy is an efficient procedure in patients with undiagnosed exudative pleurisy. Rigid or flexible forceps have been widely used for this procedure. Recently, the use of cryo-techniques was reported in pleural biopsy during semi-rigid thoracoscopy; however, the feasibility and safety of pleural cryobiopsy in elderly patients have not yet been fully elucidated. Case reports: We describe two elderly patients who safely underwent semi-rigid thoracoscopic cryobiopsy and were diagnosed with tuberculous pleurisy. Both were >85 years of age, and chest auscultation revealed reduced breath sounds in the right lower zones. Laboratory investigations revealed an elevated level of C-reactive protein without leukocytosis in both patients. Computed tomography scan of the chest revealed right pleural effusion in both patients. Pleural fluid biochemical analysis results were indicative of an exudate. Sputum cultures demonstrated no bacterial growth and smears were negative for the presence of acid-fast bacilli. For definitive diagnosis, pleural biopsy was performed via thoracoscopic cryobiopsy. Specimens obtained from the cryoprobe demonstrated 200-300-μm caseating and non-caseating epitheloid cell granulomas with Langerhans type giant cells. Based on the above results, both patients were diagnosed with TB pleurisy. Anti-tuberculosis treatment resulted in good clinical outcome in both patients. Conclusion: Cryobiopsy is easier and more efficient than biopsy with conventional forceps. Our findings in these patients suggest that semi-rigid thoracoscopic cryobiopsy might be a useful alternative diagnostic method for undiagnosed pleural effusion in elderly patients.